The Influence Of Digital Marketing Communication on Customer Decision Regarding Periodic Servicing of passenger Vahicles at PT. Budi Berlian Motor Natar - Agus Tina Simanjuntak; budhi waskito; Denu Poyo; Arie Purnama (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Bandar Lam, 2026)
Digital marketing communication is one of the strategies employed by automotive companies to influence customer decisions regarding periodic vehicle servicing. This study aims to analyze the impact of digital media, digital media messages, talent, and customer characteristics on the decisions of passenger vehicle owners to undergo periodic servicing at PT. Budi Berlian Motor Natar, a quantitative approach utilizing an exit poll survey method was adopted. Data were collected via questionnaires distributed to 105 customers undergoing periodic servicing, selected through purposive sampling. Data analysis was performed using IBM SPSS Statistics 27, encompassing validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination. The results indicate that digital media, digital media messages, talent, and customer characteristics each exert a positive influence on customer decisions. Collectively, these four variables significantly influence customer decisions, with customer characteristics emerging as the most dominant factor. The study concludes that the effectiveness of digital marketing communication in driving customer decisions to undergo periodic servicing depends not only on the utilization of digital media and message quality but also on the alignment of communication strategies with customer characteristics. These findings are expected to provide valuable insights for the company in developing more effective digital marketing communication strategies to increase customer decisions regarding periodic servicing